Experimental analysis of the SHBT approach for the dynamic modeling of a composite hollow shaft. (15th March 2020) - Barbosa, Paulo C.P.F.; Del Claro, Vergílio T.S.; Sousa, Marcelo S.; Cavalini, Aldemir A.; Steffen, Valder
Abstract: Composite materials have been extensively used in engineering applications over the past few decades, enabling new possibilities for engineering design. The limitations faced by composites have been eliminated through the development of new resins, fibers, and configurations. Thus, composite shafts appear to be an interesting solution for many rotating machinery applications due to their associated low weight, high-strength, high-temperature resistance, mechanical properties manipulation, and thermal cycling resistance as compared with metallic shafts. For the modeling of composite shafts, simplified theories are often used. In the present contribution, a finite element model (FE model) based on the Simplified Homogenized Beam Theory (SHBT) was used to predict the dynamic behavior of a thick-walled composite hollow shaft. The FE model of the shaft is based on the Timoshenko beam theory. A test rig presenting a thick-walled carbon-epoxy composite hollow shaft, two aluminum discs, and two self-aligning ball bearings was used to validate the mentioned FE model. In this case, numerical and experimental frequency response functions (FRFs) and unbalance responses were compared. Results show promising outcomes from the considered FE model regarding the prediction of the first critical speed and the corresponding unbalance responses of the composite rotor.